Enhanced detection of lymphovascular invasion in small rectal neuroendocrine tumors using D2‐40 and Elastica van Gieson immunohistochemical analysis. (17th October 2016) - Kitagawa, Yoshiyasu; Ikebe, Dai; Hara, Taro; Kato, Kazuki; Komatsu, Teisuke; Kondo, Fukuo; Azemoto, Ryousaku; Komoda, Fumitake; Tanaka, Taketsugu; Saito, Hirofumi; Itami, Makiko; Yamaguchi, Taketo; et al.
Abstract: Rectal neuroendocrine tumor (RNET) lymphovascular invasion (LVI) is regarded as an important predictor of nodal metastasis after endoscopic resection (ER). However, little is known about the frequency of immunohistochemical detection of LVI in RNETs. This study was performed to establish the actual detection of LVI rate in RNETs ≤10 mm and to evaluate associated clinical outcomes. We retrospectively reviewed the records for 98 consecutive patients treated by ER with a total of 102 RNETs ≤10 mm. Tissue sections were labeled with hematoxylin–eosin (HE) stain, the D2‐40 monoclonal antibody to evaluate lymphatic invasion, and Elastica van Gieson (EVG) stain to detect venous invasion. LVI detection rate by HE versus immunohistochemical analysis was compared. Follow‐up findings and clinical outcomes were also evaluated for 91 patients who were followed for ≥12 months. Lymphatic and venous invasion were detected using HE staining alone in 6.9% and 3.9% of patients, respectively, whereas they were detected using D2‐40 and EVG staining in 20.6% and 47.1% of the patients, respectively. Thus, the LVI detection frequency using D2‐40 and EVG staining (56.9%) was significantly higher than with HE (8.8%). Two out of seven patients who required additional surgery had regional lymph node metastases. However, among the 84 patients who were followed up without surgery, no distant metastases or recurrences were detected. Compared with HE staining, immunohistochemical analysis significantly increased the frequency of LVI detection in RNETs ≤10 mm. However, the clinical impact of LVIs detected using immunohistochemical analysis remains unclear. Clarification of the actual role of LVI using immunohistochemical analysis requires a patient long‐term follow‐up and outcomes. Abstract : Compared with hematoxylin–eosin (HE) staining, immunohistochemical analysis significantly increased the frequency of lymphovascular invasion (LVI) detection in RNETs. Clarification of the actual role of LVI using immunohistochemical analysis requires a patient long‐term follow‐up and outcomes.